Case report: Radiological features of a case of desmoplastic malignant mesothelioma of peritoneum - Wang, Jingchao; Deng, Heping (Frontiers in Oncology, 2024)
Desmoplastic malignant peritoneal mesothelioma (DMPM) is an extremely rare and aggressive subtype of sarcomatoid malignant mesothelioma, originating from the mesothelial lining of body cavities. It is characterized by significant local invasiveness and poor prognosis. The nonspecific symptoms of DMPM often result in delayed diagnosis. This case report presents the multimodality imaging findings of DMPM in a 58-year-old male, including ultrasound, CT, contrast-enhanced CT, magnetic resonance imaging (MRI), and 18-fluorodeoxy-glucose positron emission tomography combined with CT (18F-FDG PET/CT). These findings aim to enhance radiologists’ understanding of the imaging features and differential diagnosis of DMPM. In this case, the tumor was located in the right subdiaphragm and the right anterior and left medial lobes of the liver. Due to the patient’s history of alcoholic cirrhosis—a known risk factor for primary liver tumors—the initial diagnostic focus was on identifying a primary liver tumor with potential peritoneal invasion, overlooking other possible etiologies. However, histological results revealed that the liver lesion was secondary to invasion by DMPM. To the best of our knowledge, cases of DMPM invading the liver are exceedingly rare. This report underscores the importance of considering peritoneal tumors in the differential diagnosis when lesions involve both the peritoneum and adjacent organs, despite their rarity.